Relation of body mass index and blood pressure to subjective and objective acral temperature - Kavroulaki, D; Gugleta, K; Kochkorov, A; Katamay, R; Flammer, J; Orgül, S (Klinische Monatsblatter fur Augenheilkunde, 2009)
Vascular dysregulation, indicated by a positive history of cold extremities, has been postulated as a risk factor for a number of ocular diseases. In order to further characterize the phenotype of vasospastic persons, we tested the association between cold extremities, body mass index (BMI) and blood pressure (BP) in a cohort of healthy subjects. Questionnaire data were collected from one hundred and seventeen healthy subjects. Based on the history of cold hands and feet they were divided in three groups, reporting "never", "sometimes" and "always" having cold extremities. BP was measured sphygmomanometrically and as an objective measure of finger temperature, it was recorded at the fingertips with an infrared thermometer (IRT). Two-way analysis of variance with gender as one, and group selection as the second factor was performed separately for BMI and mean BP. The correlation of finger temperature with BMI and BP was analyzed by the Pearson regression. Gender distribution was male/female = 41/16, 13/21 and 4/22, for the three groups, respectively, and average age 45.8 +/- 13.0 years. For BMI, factor groups was highly significant (p = 0.0012) with both genders behaving comparably (interaction p = 0.18). For BP the corresponding p values were: factor group p = 0.026, interaction p = 0.89. Correlation coefficients between IRT and BMI were 0.34 (p = 0.0002) and between IRT and BP 0.24 (p = 0.009). A statistical significant association is present in healthy subjects between body mass index and blood pressure on one, and cold extremities on the other side, defined subjectively as well as measured objectively. This relationship is gender-independent.